2023
DOI: 10.1039/d3tc01458d
|View full text |Cite
|
Sign up to set email alerts
|

Continuous synthesis of all-inorganic low-dimensional bismuth-based metal halides Cs4MnBi2Cl12 from reversible precursors Cs3BiCl6 and Cs3Bi2Cl9 under phase engineering

Abstract: Continuous synthesis of all-inorganic, low-dimensional, bismuth-based metal halides Cs4MnBi2Cl12 with high PLQY from reversible precursors Cs3BiCl6 and Cs3Bi2Cl9 under phase engineering and application of an orange light source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…No additional diffraction peaks were present (Figure S3). The excitation/emission spectra of Cs 4 Cd 0.7 Mn 0.3 Bi 2 Cl 12 consisted of three parts; the UV broadband excitation spectrum is caused by the partially allowed 1 S 0 → 3 P 1 transition of Bi 3+ , and two PLE split peaks at 320 and 360 nm are attributed to lattice vibration and the Bi 6p-cl dynamic Jahn–Teller distortion effect of excited states caused by 3p antibond orbital coupling, while PLE peaks at 430 and 520 nm are attributed to spin-abstaining transitions 6 A 1 → 4 T 2 and 6 A 1 → 4 T 1 of Mn 2+ , respectively (Figure a). , It can be seen that the emission spectrum exhibits an Mn 2+ -characteristic broadband orange-yellow luminescence, which is attributed to the characteristic 4 T 1 → 6 A 1 transition of Mn 2+ . , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No additional diffraction peaks were present (Figure S3). The excitation/emission spectra of Cs 4 Cd 0.7 Mn 0.3 Bi 2 Cl 12 consisted of three parts; the UV broadband excitation spectrum is caused by the partially allowed 1 S 0 → 3 P 1 transition of Bi 3+ , and two PLE split peaks at 320 and 360 nm are attributed to lattice vibration and the Bi 6p-cl dynamic Jahn–Teller distortion effect of excited states caused by 3p antibond orbital coupling, while PLE peaks at 430 and 520 nm are attributed to spin-abstaining transitions 6 A 1 → 4 T 2 and 6 A 1 → 4 T 1 of Mn 2+ , respectively (Figure a). , It can be seen that the emission spectrum exhibits an Mn 2+ -characteristic broadband orange-yellow luminescence, which is attributed to the characteristic 4 T 1 → 6 A 1 transition of Mn 2+ . , …”
Section: Resultsmentioning
confidence: 99%
“…Doping with a low content of activated ions is an effective strategy to improve the photoluminescence performance of all-inorganic halide perovskites. Transition metal ions Mn 2+ and main group ions Sb 3+ and Te 4+ are dopants known to exhibit excellent optical properties, including broadband emission across the visible spectrum and their efficient PLQY, which showed potential to be used in the construction of pc-LEDs. Wu et al showed energy transfer from Cs 3 Sb 2 Cl 9 to the Mn 3d state, resulting in d–d transition and bright red luminescence . Xia et al achieved efficient broadband yellow light emission by doping Sb 3+ into zero-dimensional air-stable lead-free Cs 2 InCl 5 (H 2 O) crystals, with a photoluminescence quantum yield of up to 95.5% …”
Section: Introductionmentioning
confidence: 99%
“…Lead halide perovskites, especially CsPbX 3 (X = Cl – , Br – , or I – ), have become popular materials for various optoelectronic device applications for their ultrahigh photoluminescence quantum yield (PLQY), high absorption coefficient, narrow half-peak full width, and broad color range of emission. However, the inherent toxicity and instability associated with lead halide are a concern. Alternative strategies are to use heterosubstitution of two Pb 2+ with a monovalent cation (Ag + , Na + ) and trivalent cations (In 3+ , Bi 3+ , Sb 3+ ) or a tetravalent cation (Sn 4+ , Zr 4+ , Te 4+ ) to produce stable and nontoxic fully inorganic lead-free vacancy-ordered double perovskites or low-dimensional metal halide perovskites. …”
Section: Introductionmentioning
confidence: 99%
“…One feasible strategy is to replace Pb 2+ ions with trivalent ions, such as Bi 3+ , In 3+ , or Sb 3+ , in the form of low-dimensional metal halides, such as Cs 3 A 2 X 9 or Cs 3 AX 6 (A = Bi 3+ , In 3+ , or Sb 3+ ; X = Cl – , Br – , or I – ). Lead-free metal halide perovskites have been shown to have great potential in applications of high-performance optoelectronic devices, including photodetectors, light-emitting diodes, field-effect transistors, solar cells, photocatalysis, etc. Another feasible strategy is to substitute two Pb 2+ ions with a monovalent cation (Ag + or Na + ) and one of the trivalent cations (In 3+ , Bi 3+ , or Sb 3+ ) or with a tetravalent cation (Sn 4+ , Zr 4+ , or Te 4+ ) to produce an all-inorganic lead-free double perovskite phosphor. Stable and nontoxic vacant ordered double perovskites have been widely studied with regard to photoelectricity. Examples include photodetectors, light-emitting diodes, field-effect transistors, solar cells, photocatalysis, etc. …”
mentioning
confidence: 99%
“… , It is well-known that Ln ions are very sensitive to excitation light sources of different wavelengths. The PL spectral measurement of Cs 2 NaScCl 6 :Er 3+ revealed that although large differences in luminous intensity do exist under various types of excitation ranging from 280 to 420 nm, the peak shapes were very similar, indicating that the luminescence of Er 3+ originated from the same energy transfer pathway. ,, Here, we propose a possible photophysical mechanism, as shown in Figure f, under 380 nm ultraviolet excitation, in which the electrons are excited to the 4 G 11/2 state and then the electrons of the excited state gradually return to the ground state through the relaxation process, resulting in the narrowband luminescence characteristic of the Er 3+ 4f–4f luminescence from the visible to NIR region.…”
mentioning
confidence: 99%